2014
DOI: 10.3174/ajnr.a4191
|View full text |Cite
|
Sign up to set email alerts
|

Extra-Aneurysmal Flow Modification Following Pipeline Embolization Device Implantation: Focus on Regional Branches, Perforators, and the Parent Vessel

Abstract: BACKGROUND AND PURPOSE: Flow-diverter technology has proved to be a safe and effective treatment for intracranial aneurysm based on the concept of flow diversion allowing parent artery and collateral preservation and aneurysm healing. We investigated the patency of covered side branches and flow modification within the parent artery following placement of the Pipeline Embolization Device in the treatment of intracranial aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 43 publications
2
49
0
Order By: Relevance
“…Neurologic deficit is rare after branch occlusion by FDS placement. [13][14][15] Two patients in the series from Gascou et al 13 had…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurologic deficit is rare after branch occlusion by FDS placement. [13][14][15] Two patients in the series from Gascou et al 13 had…”
Section: Discussionmentioning
confidence: 99%
“…There are limited studies of posterior circulation aneurysms treated with FDSs, only one of which (Gascou et al 13 ) specifically reported the patency of the PICA. This series of 59 patients with 66 aneurysms in various locations found a 3% overall occlusion rate and 16.2% branch vessel stenosis rate at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The reported issues associated with flow diversion concern nearly exclusively the treatment efficacy and its delayed complications (aneurysm rupture after treatment, side branch occlusion), which are basically related to hemodynamic changes, biologic factors, and medication strategies. 33,34 However very few reports are dedicated to procedural complications and, in particular, the implantation and the deployment concerns of such complex devices. Due to its woven structure and its high wire …”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] To date, knowledge on the anatomic status of the post-PED vascular segment as revealed on DSA is mainly limited to within 6 -12 months. 1,2,4,5,7,8 Follow-up DSA with a longer duration of 18 -24 months has been reported in only 2 studies. 6,9 Beyond 24 months, post-PED vascular status has been studied only with MR imaging, 10 but CT angiography or MR angiography is not desirable for this purpose owing to metal artifacts from the PED and suboptimal spatial resolution.…”
mentioning
confidence: 99%